Influence of the Membrane Anchoring and Cytoplasmic Domains on the Fusogenic Activity of Vesicular Stomatitis Virus Glycoprotein G - Odell, Derek A. (My University, 1998)
Relatively little is known about the vesicular stomatitis virus (VSV) glycoprotein G fusion mechanism. Vesicular stomatitis virus has a single type 1 integral membrane glycoprotein G embedded in the viral membrane. It is the only viral protein required for VSV induced low pH mediated fusion. Mutations in four regions (H2, A5, A4 and HI0) of the VSV G ectodomain have been shown to abolish the fusion activity of the viral glycoprotein (Li et al.,l993). One region H2 (a.a 117-139) has been suggested to be the fusion peptide (Zhang and Ghosh, 1994)(Fredericksen and Whitt, 1995). Amino acids 59-221 of the G protein, an area that encompasses the H2 region, has recently been shown to interact with liposomes through hydrophobic photolabeling experiments (Durrer et al., 1995), suggesting that the H2 region (fusion peptide)is able to interact with hydrophobic target bilayers at low pH. A soluble VSV G protein lacking the transmembrane anchor and cytoplasmic tail of VSV G is not fusogenic, suggesting that G must be anchored to the plasma membrane to promote syncytia (Florkiewicz and Rose, 1984). To better understand the steps involved in the fusion mechanism of VSV G it is important to identify domains within the protein that are involved in the fusion process. To determine the contributions of the transmembrane anchor and cytoplasmic tail to the VSV fusion mechanism chimeric G proteins were constructed. The transmembrane anchor alone or in conjunction with the cytoplasmic tail ofVSV G was replaced with equivalent domain from other viral proteins, HSV-1 glycoproteins gB and gD, adenovirus E3 11.6 K gene, that are not involved in low-pH fusion and the cellular protein CD4. All chimeras were expressed in COS-1 cells, glycosylated, oligomerized, transported to the cdl surface, showed a low-pH induced conformational change and were expressed on the cell surface at levels equivalent to wild-type G. The transmembrane hybrids show extensive syncytia formation at levels similar to wild-type G when induced at pH 5.6. The transmembrane-cytoplasmic tail hybrids showed reduced levels of syncytia as compared to wild-type Gat both pH 5.6 and 5.2. A glycosylphosphatidylinositollipid-anchored ectodomain of G (GGPI), which lacks both the transmembrane and cytoplasmic tail ofG, was expressed in COS-1 cells. The GGPI chimera was glycosylated, expressed on the cell surface,and oligomerized similar to wild-type G. However the chimera was fusion negative, could not promote lipid mixing and h~,d an altered tryptic digestion profile. A fusion negative chimera Gt12gBwas constructed by exchanging the TM of G with the equivalent domain from HSV-1 gB TM plus eight extra amino acids of the gB ectodomain. Deletion of the 11 extra gB amino acids (GgB3G) restored the fusogenic activity of this chimera. Another chimera G 10 DAF directly demonstrated that the fusion negative phenotype of GGPI, like chimera Gtii1Lll2gB, was a result of the 10 extra amino acids at the EC-TM interface. The ectodomain (EC)-transmembrane (TM) interface is highly conserved among 5 vesiculoviruses. Chimeras with a 9 amino acid insertion (GlODAF), deletion (G~9) or replacement (G~910DAF) were expressed in COS-1 cells. The expressed proteins were glycosylated, underwent a low-pH induced conformational change and were expressed on the cell surface at levels equivalent to wild type, but were fusion negative. Suggesting that both the sequence and spatial arrangement of amino acids at the EC-TM interface may affect VSV G fusion. Taken together the data suggests that the specific amino acid sequence of the transmembrane anchor of VSV G is not essential for fusion. Replacement of the TM of VSV G with equivalent domains from other viral and cellular proteins does not affect the fusion activity. The cytoplasmic tail of VSV G may form an entity alone or in conjunction with the transmembrane anchor that can regulate fusion. Another region in the ectodomain of VSV G renders the glycoprotein fusion sensitive in a cell-cell fusion assay and was characterized at the EC-TM interface.
Keywords: membrane anchoring; cytoplasmic domains; fusogenic activity; vesicular stomatitis; virus glycoprotein g